Efektivitas Pembelajaran Berbantuan Simulasi Virtual Lab Terhadap Peningkatan Pemahaman Konsep Pada Materi Pengukuran Kelas X (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
This study aims to determine the effectiveness of Virtual Lab simulation-assisted learning in improving conceptual understanding of measurement material for grade X high school students. The study used a quasi-experimental method with a pretest-posttest control group design. The study sample consisted of two classes, namely the experimental class that received learning using Virtual Lab simulation and the control class that received conventional learning. The instrument used was a conceptual understanding test given before and after learning. Data analysis was carried out using the N-Gain test to determine the level of improvement in students' conceptual understanding. The results showed that the average N-Gain value in the experimental class was in a higher category than the control class. This finding indicates that Virtual Lab-assisted learning is able to provide a more significant increase in conceptual understanding than conventional learning. Thus, the use of Virtual Lab simulation can be used as an alternative effective learning media in supporting the physics learning process, especially in measurement material. This study also provides an illustration that the integration of technology in learning can improve student interaction, understanding, and motivation..